Registration as legal mechanism to sustain institution of marriage - Md Hashim, Noraini (2011)
In Malaysia, different societies express themselves in different ways in performing a marriage ceremony. The non-Muslims in Malaysia practices the dual system of marriage (namely the customary marriage and the civil law of marriage), up to 1 March 1982. After that date, the Law Reform (Marriage and Divorce) Act 1976 came into effect, and is practised until today. Previously, marriage under the Chinese customary law was recognised in Peninsular Malaysia by the application of the principle that where the local law was wholly unsuited to the conditions of the parties, due to peculiarities of religious opinion and usages, then their own laws and or usages were applied to them. As such, it is observed that the validity of a Chinese customary marriage merely requires a consensual marriage and the requirements of a ceremony and a repute of marriage are evidentiary only and not essential. Unlike the Chinese customary marriage, the priest solemnising the marriage and the expert evidence findings, relating to the rites and ceremony rather than the mere intention to form a permanent union, determines the validity of a Hindu marriage. The discussion proves that requirement of registration is introduced as a medium to facilitate proof of marriage for the non-Muslims. It is initiated to avoid uncertainty relating to the status of marriage especially involving marriage solemnized according to customs. The objective of this paper is to establish that the requirement of registration of marriage is vital for the sustenance of marriage. It is to manage legal issues pertaining to it and to avoid disputes, which may give rise to uncertainty in terms of whether a marriage has occurred. It is also to enlighten the people at large the importance of registration as a legal protection mantle assisting them (especially the wives and children) when matrimonial difficulties crop up.